A PBPK model to estimate PCDD/F levels in adipose tissue: Comparison with experimental values of residents near a hazardous waste incinerator - Schuhmacher, Marta; Fàbrega, Francesc; Kumar, Vikas; García, Francisco; Nadal, Martí; Domingo, José L. (Environment international, 2014)
This study was aimed at determining the concentrations of polychlorinated dibenzo-p-dioxins and polychlorinated dibenzofurans (PCDD/Fs) in 15 samples of adipose tissue from subjects who had been living in the vicinity of a hazardous waste incinerator (HWI). The results were compared with levels obtained in previous surveys carried out in 1998 (baseline study), 2002 and 2007. The current (2013) concentrations of PCDD/Fs in adipose tissue ranged from 2.8 to 46.3pg WHO-TEQ/g fat (mean and median concentrations: 11.5 and 7.4pg WHO-TEQ/g fat, respectively), being significantly lower (64%) than those observed in 1998. In contrast, no significant differences in the mean PCDD/F concentrations were noted in the period 2002–2013. The significant decrease of the PCDD/F content in fat, also noted in other biological monitors such as plasma and breast milk, is in agreement with the reduction in the dietary intake of PCDD/Fs found in the same area of study. Similarly to other investigations across Europe, an increase of PCDD/F levels in adipose tissue in relation to age was observed, while no significant differences were noted according to gender. A multicompartmental physiologically-based pharmacokinetic (PBPK) model was also applied to estimate the levels of PCDD/Fs in adipose tissue. When comparing the modeled and experimental concentrations of PCDD/Fs in that tissue, very similar values were obtained for the four surveys, which indicates this can be a reliable tool to predict the internal dose of PCDD/Fs. •A significant temporal reduction of PCDD/Fs in adipose tissue was found in adults.•This reduction is in agreement with the decrease in the dietary intake of PCDD/Fs.•PBPK modeling can be a reliable tool to estimate the body burdens of PCDD/Fs.